Accuracy of recall of musculoskeletal injuries in elite military personnel: a cross-sectional study. Issue 12 (14th December 2017) - Lovalekar, Mita; Abt, John P; Sell, Timothy C; Lephart, Scott M; Pletcher, Erin; Beals, Kim
Abstract : Background: Self-reported data are often used in research studies among military populations. Objective: The accuracy of self-reported musculoskeletal injury data among elite military personnel was assessed for issues with recall. Design: Cross-sectional study. Setting: Applied research laboratory at a military installation. Participants: A total of 101 subjects participated (age 28.5±5.6 years). Study participants were active duty military personnel, with no conditions that precluded them from full duty. Primary and secondary outcome measures: Self-reported and medical record reviewed injuries that occurred during a 1-year period were matched by anatomic location, injury side (for extremity injuries), and injury year and type. The accuracy of recall was estimated as the per cent of medical record reviewed injuries correctly recalled in the self-report. The effect of injury anatomic location, injury type and severity and time since injury, on recall, was also assessed. Injuries were classified as recent (≤4 years since injury) or old injuries (>4 years since injury). Recall proportions were compared using Fisher's exact tests. Results: A total of 374 injuries were extracted from the subjects' medical records. Recall was generally low (12.0%) and was not different between recent and old injuries (P=0.206). Injury location did not affect recall (P=0.418). Recall was higher for traumatic fractures as compared with less severe non-fracture injuries (P values 0.001 to <0.001). Recall for non-fracture injuries was higher for recent as compared with old injuries (P=0.033). This effect of time since injury on recall was not observed for fractures (P=0.522). Conclusions: The results of this study highlight the importance of weighing the advantages and disadvantages of self-reported injury data before their use in research studies in military populations and the need for future research to identify modifiable factors that influence recall.